CELEBGRAM ENDORSEMENT AND PRODUCT QUALITY, HOW DOES IT INFLUENCE THE INTEREST TO SHOP ONLINE? - Irham Amir; Alma Widiyanti (FORBISWIRA FORUM BISNIS DAN KEWIRAUSAHAAN - SINTA 4, 2023)
This research aims to determine the effect of the endorsement and product quality on online shopping interest on the cosmetic brand EMINA. By using a descriptive quantitative approach, the sampling technique used is random sampling by distributing questionnaires to 100 millennial generation women in Bogor. This study found the endorsement program and product quality have a positive and significant effect on online shopping interest.